A case study in strategic decision making using multi-criteria decision making and balanced scorecard. (26th July 2022) - Ajripour, Iman; Molnar, Viktor
The well-known model for supporting strategic management, the balanced scorecard (BSC), has proved to be a useful tool in strategic planning. Several decision-making models are available to support managerial decisions. In this paper BSC and some ranking methods are combined to increase the efficiency of strategic decisions. The elaborated model was adapted in a real-life decision-making situation and tested by the case study method. Based on the results the decision makers who participated in the research elaborated a course of action for reaching the strategic management goal of increasing management efficiency performance.